Microstructure and properties of ZrO2/Ni3Al-Ni3Al double-layer coating on stainless steel prepared by powder sintering one-step forming process. (17th November 2021) - Li, Xinxing; Yang, Zirun; Wang, Hongxia; Li, Lin; Ren, Naifei
Abstract: ZrO2 /Ni3 Al-Ni3 Al double-layer coating on stainless steel was prepared by powder sintering one-step forming process. The surface-interface morphologies, chemical element distribution and phase compositions of the coatings before and after thermal oxidation or hot corrosion were analyzed using scanning electron microscope (SEM), energy dispersive spectrometer (EDS) and X-ray diffractometer (XRD). The microstructure of the coating was Ni3 Al matrix with dispersed ZrO2 particles, which was pure and compacted. The Ni3 Al intermediate layer compactly formed between stainless steel substrate and ZrO2 /Ni3 Al composite coating, with good metallurgical bonding interfaces. The ZrO2 /Ni3 Al-Ni3 Al double-layer coating exhibited a relatively high outmost microhardness of about 500 HV, and then gradually decreased from the coating to the substrate. When thermal oxidized or hot corroded at 1050 °C, a mixed oxide layer of NiO, Al2 O3 and NiAl2 O4 formed on the coating surface, which effectively acted as a diffusion barrier for oxygen and corrosive substances, and thus demonstrated the good protective effect of ZrO2 /Ni3 Al coating.